2018
DOI: 10.1016/j.cherd.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser sintering of ceramic powders with bimodal particle size distribution

Abstract: This paper addresses the possibility of carrying out Selective laser sintering (SLS) using powders obtained as mixtures of particles of different size. The beam source used in the experiments was a CO2 laser tube with a nominal power of 40W. The materials used were model Glass beads and a real ceramic material characterized by irregular shape of the particles. Bimodal distributed powders were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 37 publications
(57 reference statements)
0
19
0
2
Order By: Relevance
“…Although there has been much investigation on the influence of process parameters and material compounds on the mechanical properties of polymers such as PA12 [4,5,6,7], the effect of the powder deposition process is not yet well understood. For this purpose, a number of experimental and numerical related approaches helped to gain new insights into the topic of creating dense packings and made it possible to better evaluate the powder flow properties [8,9,10,11,12]. Further investigations, such as the determination of appropriate particle sizes for SLS [13] and particle size distributions (PSD) [10], along with new ways of quantifying powder flow properties [12,14] showed that powder characterization still lacks appropriate methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been much investigation on the influence of process parameters and material compounds on the mechanical properties of polymers such as PA12 [4,5,6,7], the effect of the powder deposition process is not yet well understood. For this purpose, a number of experimental and numerical related approaches helped to gain new insights into the topic of creating dense packings and made it possible to better evaluate the powder flow properties [8,9,10,11,12]. Further investigations, such as the determination of appropriate particle sizes for SLS [13] and particle size distributions (PSD) [10], along with new ways of quantifying powder flow properties [12,14] showed that powder characterization still lacks appropriate methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms, i.e. dissolution-crystallisation [8], sintering [9,10] and supersaturations (Ostwald caking [11]) are responsible for solid bridges. In sintering [9], particles coalesce, by bridging between two or more particles.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…PA12 nylon sample was collected and undergo size analysis. The tabulation size of PA12 powder before SLS 3D printing process were analysed to measured particulate matter exposed during powder preparation phase [30].…”
Section: Characterizationmentioning
confidence: 99%